Evaluation of the quality of urban public transport by using the Combinex method - Borbás, Péter Dániel (Studia Mundi – Economica, 2021)
The quality of urban public transport services has become an important factor in improving the acceptance of public transport and reducing the use of individual cars. The service quality can be examined from several aspects. Typically, the expectations of user are partly included in the system of quality criteria defined by the responsible public authority. The aim of the analysis is to show, through a concrete example, how the quality of an urban public transport service can be evaluated by using a selected multifactor decision analysis method (Combinex). The study is based on the specific expectations (public service requirements) in the public transport service system of Budapest and analyzes the data on the actual performance of the transport service provider. With the help of the method, the weighted data of the quality indicators were aggregated, and the characteristic values of the examined periods were compared and the results were evaluated. Overall, the analysis of the performance of the tram sector shows that the quality indicators of the public service contract have different priorities, but based on the actual data of recent years, further improvements are needed in passenger comfort.